KONSEP MANUSIA DALAM TEORI PSIKOANALISIS HUMANIS DIALEKTIK ERICH FROMM - Theguh Saumantri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Erich Fromm was a psychoanalyst, social theorist, and philosopher. In the course of his life fromm studied about the human personality, therefore fromm in his humanist theory showed his concern for the struggle of the human being who never gave up on obtaining freedom in relation to the human need to relate to others. This study aims to understand the meaning, urgency and nature of human needs in the dialectical humanist psychoanalysis theory of erich fromm as the capital of human self-existence in this world and read the erich fromm framework of thought which is seen as having a great influence on human personality. Using a descriptive analysis approach, the conclusion is that the concept of munusia in the perspective of his theory is viewed as a form of human consciousness. Man has a unique suprabiological nature and is built in human character. Human life is determined by the inevitable alternative between returning to animal existence or arriving at a true human existence.